Gaya Percintaan Remaja dalam Novel Dilan Dia adalah Dilanku Tahun 1991Karya Pidi Baiq: Tinjauan Sosiologi Sastra - Shilfina Fauzia; Laura Andri Retno Martini; Khothibul Umam (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
The novel Dilan Dia Adalah Dilanku in 1991 by Pidi Baiq contains a distinctive style of expressing different teenage romance. The purpose of this study is to describe the teenage love style in the novel Dilan Dia adalah Dilanku in 1991 by Pidi Baiq. This research is a library research because the object of the research is library materials, namely the 1991 novel Dilan Dia adalah Dilanku. The focus of this research is the 90s teenage romance style of Dilan and Milea characters, in the 1991 novel Dilan Dia adalah Dilanku is a romance genre novel. The theory used is the structural theory of fiction and the theory of love. The theory of love put forward by Erich Froom who has a famous theory, namely The Art of Loving.  The results of this study are the structural elements contained in the 1991 novel Dilan Dia adalah  Dilanku which include; plot and plot, characters and characterizations, setting and court, as well as the style of youth romance contained in the novel Dilan Dia adalah Dilanku 1991 by Pidi Baiq which includes; Attention, responsibility, respect, knowledge. Keywords: Stenberg's Theory of Love, Romance Style, Novel.